What Can Government Do to Help SMEs’s Product Sales through Halal Certificate? - Abdul Muhaimin Elyusufi; Maratun Saadah; Nugraha Nugraha; Maya Sari; Triyono Adi Tristanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Halal is an important concept that facilitates and simplifies the consumption of food and beverage products, particularly for Muslim consumers. For a Muslim consumer, halal foods and drinks mean that the product has met the Shariah law requirements, whereas for a non-Muslim consumer, it represents the symbol of hygiene, quality, and safety when produced strictly under the Holistic Halal Assurance Management System. As a result, today's consumers are extremely concerned and are constantly conscious of what they eat, drink, and use. Muslim and non-Muslim consumers' awareness describes their perception and cognitive reaction to products or foods on the market. According to the study, developing Halal is a communally obligatory (fardhu kifayah) for Small Medium Enterprises (SMEs) and a personally obligatory (fardhu ain) for Muslim consumers. The Indonesian government has already recognized the importance of SMEs by implementing various policies and action plans, as well as introducing Halal-related programs to assist SMEs.